Elucidando as lacunas de conhecimento de Myrtaceae nos remanescentes de Cerrado e Mata Atlântica no município de Cunha, SP, Brasil. - Maruyama, Adriano da Silva de Cicco (2023)
Myrtaceae is the largest family of the order Myrtales, and comprises 145 genera ca. 5970 species. The Municipality of Cunha is one of the largest in the State of São Paulo, and is located in the upper Paraíba, close to the border with the municipality of Paraty, Rio de Janeiro, with an area of 1,407 km² and inserted in areas known as “Mares de Morros”. This study was based on fieldwork and consultation of specimens from herbaria. Morphological analyzes were performed using a 30X magnifying glass using dry and fresh specimens. More than 2210 specimens were analyzed, most of which were collected mainly by the first author of this work in the municipality of Cunha. The consulted herbaria were visited in person (ESA, BOTU, HRCB, SORO, SP, SPF, SPSF, UEC) or virtually (online, via SpeciesLink (http://inct.splink.org.br/), Jardim Botânico do Rio de Janeiro (http://www.jbrj.gov.br/jabot) and reflora (http://reflora.jbrj.gov.br/reflora/herbarioVirtual/). Eleven genera and 144 species were found: Myrcia (53 spp.), Eugenia (41 spp.), Myrceugenia (16 spp.), Campomanesia (9 spp.), Psidium (9 spp.), Myrciaria (5 spp.), Neomitranthes (3 spp.), Siphoneugena (3 spp.) and Plinia (3 spp.), Blepharocalyx (1 sp.) and Pimenta (1 sp.). Three new records for São Paulo are presented: Myrcia pulchella, Myrciaria disticha and Plinia delicata. New distribution delimitations for the state of São Paulo is referred for Eugenia astringens, E. aurata, E. expansa, E. myrcianthes, Myrcia bella, M. chrysotrichoma, M. diaphana, M. neoclusiifolia, M. neoregeliana, M. strigipes, M. uberavensis and Neomitranthes pedicellata. The first record of fruits is presented for Eugenia longibracteata, Myrcia curta, Neomitranthes capivariensis, N. pedicellata and Pimenta pseudocaryophyllus var. hoehnei. Eugenia disperma, Myrceugenia kleinii, Neomitranthes pedicellata and Myrcia rupicola are endangered species registered for the municipality of Cunha.